2012
DOI: 10.1109/tcbb.2012.110
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of the Set of Species Trees that Produce Anomalous Ranked Gene Trees

Abstract: Abstract-Ranked gene trees, which consider both the gene tree topology and the sequence in which gene lineages separate, can potentially provide a new source of information for use in modeling genealogies and performing inference of species trees. Recently, we have calculated the probability distribution of ranked gene trees under the standard multispecies coalescent model for the evolution of gene lineages along the branches of a fixed species tree, demonstrating the existence of anomalous ranked gene trees (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…The ranked gene tree in Figure 1(A) matches the ranked species tree, while the ranked gene tree in Figure 1(B) does not. In spite of the results of this paper, caterpillar gene trees can be ARGTs (Degnan et al, 2012a), i.e., a caterpillar gene tree can be more probable than a matching ranked gene tree, even though it must be less probable than the matching unranked gene tree.…”
Section: Anomalous Ranked and Unrooted Gene Treesmentioning
confidence: 60%
See 2 more Smart Citations
“…The ranked gene tree in Figure 1(A) matches the ranked species tree, while the ranked gene tree in Figure 1(B) does not. In spite of the results of this paper, caterpillar gene trees can be ARGTs (Degnan et al, 2012a), i.e., a caterpillar gene tree can be more probable than a matching ranked gene tree, even though it must be less probable than the matching unranked gene tree.…”
Section: Anomalous Ranked and Unrooted Gene Treesmentioning
confidence: 60%
“…Recently, the concept of anomalous gene trees has also been extended to ranked gene trees (Degnan et al, 2012a;Disanto and Rosenberg, 2014) and unrooted gene trees (Degnan, 2013).…”
Section: Anomalous Ranked and Unrooted Gene Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…While a robust phylogeny is needed to study diversification and adaptation in such groups, phylogenetic analysis of close relatives can be problematic. Discordance between gene trees and species trees is more likely when speciation is recent and the effective population size of the ancestral population is large relative to the age of the species (Kubatko and Degnan 2007; Degnan et al, 2012). This discordance can arise through hybridization, gene duplication and loss, and incomplete lineage sorting (Maddison 1997; Degnan and Rosenberg 2009; Knowles and Kubatko 2010; Nakhleh 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is in spite of the fact that simple formulas exist for relating the number of duplication-loss events and the number of deep coalescence events (Zhang 2011), which, at first glance, might suggest that parsimony methods would always infer one event over the other (for further discussion, see Supplemental Material S5). Furthermore, while we have demonstrated that DLCpar performs well under a variety of species tree parameters, more study is needed in the ''anomaly zone'' of species histories in which anomalous gene trees (AGTs) exist, that is, where the gene tree most likely to evolve under a coalescent model differs from the species tree topology (Degnan and Rosenberg 2006;Degnan et al 2012;Degnan 2013). Within an anomaly zone, it has been shown that species trees reconstructed using democratic vote (Degnan and Rosenberg 2006), greedy consensus ), maximum likelihood from concatenated sequences (Kubatko and Degnan 2007), and minimizing-deepcoalescence (Than and Rosenberg 2011) methods are inconsistent, meaning that the estimated species tree topology is incorrect in the limit as the number of sampled gene trees goes to infinity.…”
Section: Discussionmentioning
confidence: 99%